Analisis Semiotika Roland Barthes Tentang Makna Pemilu Damai Dalam Film Kejarlah Janji - Silvia Dewi Anisa; M Rifa’i (Prisani Cendekia Institute, 2024)
This research aims to explore the meaning of a peaceful election as conveyed in the film